WORK EXPERIENCE, PROFESSIONALISM, INDEPENDENCE AND THE APPLICATION OF INFORMATION TECHNOLOGY ON AUDITOR PERFORMANCE IN ORDER TO INCREASING AUDIT QUALITY AT THE FINANCIAL AUDIT AGENCY OF THE REPUBLIC OF INDONESIA REPRESENTATIVE OF THE RIAU PROVINCE - Mimelientesa Irman; Erwin Agus Suhendra; Haugesti Diana (Journal of Applied Business and Technology, 2021)
This study aims to determine and analyze the influence of work experience, professionalism, independence and the application of information technology on auditor performance in improving audit quality at the Indonesian Financial Audit Board Representative of the Republic of Indonesia Riau Province. The sample in this study was the entire population of 76 respondents using the census/questionnaire method and then analyzed by Structural Equation Modeling (SEM) with the help of SPSS 26.0 and Smart PLS 3.2.9. The results of the analysis prove (1) Work Experience has no significant effect on Auditor Performance, (2) Professionalism has no significant effect on Auditor Performance, (3) Independence has a significant effect on Auditor Performance, (4) Information Technology Application has a significant effect on Auditor Performance, (5 ) Work Experience has no significant effect on Audit Quality, (6) Professionalism has a significant effect on Audit Quality, (7) Independence has no significant effect on Audit Quality, (8) Information Technology Application has no significant effect on Audit Quality, (9) Auditor Performance has an effect significant impact on Audit Quality.